The geopolitical context of forest exploitation in the Yucatan Peninsula, Mexico (2019)
This article reviews the historical framework of logging and the loss of timber wealth and the loss of forest cover in relation to rural settlement, fostered by some colonization programs and policies in the Yucatan Peninsula since the 1950s. It also analyses the efforts that are currently being made to mitigate and even reverse this situation, based on international public policies that have been assumed by the Mexican authorities. This qualitative work is a product of the review of academic and institutional literature. It makes it possible to see how the transition from extractive to sustainable forestry is still in a context in which geopolitics is a determining factor.